Challenging Diagnostic Process for a Malignant Peritoneal Mesothelioma Patient With Ascites and Pleural Effusion: A Case Report and Review of the Literature - Zeng, Xiaofeng; Xu, Ke; Zhang, Liying; Huang, Xiaoli (Frontiers in Oncology, 2022)
Malignant peritoneal mesothelioma (MPM) is a sporadic and fatal disease of the peritoneal lining. Its diagnosis has been known to be challenging, time consuming and money consuming. In this paper, we report an MPM case of a 58-year-old man with severe abdominal distension. After he had received all kinds of auxiliary examination, including computed tomography scans of the chest and whole abdomen, examinations of peripheral and pleural fluid, positron emission tomography, and twice fine-needle peritoneal biopsies, his disease still could not be confirmed. Eventually, the patient was diagnosed with MPM through laparoscopic biopsy and IHC. From this case, we concluded that clinicians can gradually discover and diagnose the disease through (1) high platelet and CA125 levels and CT imaging results; (2) cytologic examinations of ascites and pleural fluid; (3) peritoneal biopsies (fine-needle biopsy, laparoscopy biopsy); and (4) histopathological examinations and immunohistochemistry findings. The diagnostic process involved with this patient can be an example to demonstrate the effectiveness of various auxiliary examination methods in MPM diagnosis.